Patterns of Eurasian HSV-1 molecular diversity and inferences of human migrations. - Bowden, R; Sakaoka, H; Ward, R; Donnelly, P (2006)
Following our recent report of high levels of recombination and geographic structuring amongst isolates from two populations, we have investigated global patterns of herpes simplex virus type 1 (HSV-1) molecular diversity using population samples from six countries in Europe, Asia and Africa. Sequence comparisons show that HSV-1 from Kenya is both highly diverse and distinct from either European or Asian HSV-1. HSV-1 populations are much more highly differentiated than human populations at the same geographic scales, with 35% of total variation at the level of inter-population comparisons, a difference likely to be due to higher rates of both mutation and genetic drift in HSV-1 than in equivalent human data. There is substantial differentiation between northwestern European HSV-1 populations and those from East Asia, and while patterns of British and Swedish HSV-1 variation were indistinguishable, differentiation was detectable amongst Chinese, Korean and Japanese HSV-1 samples, in spite of their lower overall diversity. The program Structure was used to reconstruct ancestral Eurasian lineages, which we estimated to have originated approximately 60,000 years ago. A specific pattern detected amongst East Asian HSV-1 isolates is currently best explained by the two waves of migration responsible for the peopling of Japan.